A theory of argument - Vorobej, Mark (Cambridge University Press, 2006)
A Theory of Argument is an advanced textbook intended for students in philosophy, communications studies and linguistics who have completed at least one course in argumentation theory, information logic, critical thinking or formal logic. Containing nearly 400 exercises, Mark Vorobej develops a novel approach to argument interpretation and evaluation. One of the key themes of the book is that we cannot succeed in distinguishing good argument from bad arguments until we learn to listen carefully to others. Part I develops a relativistic account of argument cogency that allows for rational disagreement. Part II offers a comprehensive and rigorous account of argument diagramming. Hybrid arguments are contrasted with linked and convergent arguments, and a novel technique is introduced for graphically recording disagreements with authorial claims.